2013
DOI: 10.1682/jrrd.2011.09.0159
|View full text |Cite
|
Sign up to set email alerts
|

Examination of anticipated chemical shift and shape distortion effect on materials commonly used in prosthetic socket fabrication when measured using MRI: A validation study

Abstract: Abstract-The quality of lower-limb prosthetic socket fit is influenced by shape and volume consistency during the residual limb shape-capturing process (i.e., casting). Casting can be quantified with magnetic resonance imaging (MRI) technology. However, chemical shift artifact and image distortion may influence the accuracy of MRI when common socket/casting materials are used. We used a purpose-designed rig to examine seven different materials commonly used in socket fabrication during exposure to MRI. The rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Studies have shown that MRI is an accurate method of soft tissue and bone dimension and volume measurement and has been used to estimate accurate morphological information of different tissues, for example, bone, muscle, and articular cartilage [1719]. Additionally, the use of MRI in a residual limb morphological measurement, when common casting materials were used, was validated in previous experiments [15, 20, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that MRI is an accurate method of soft tissue and bone dimension and volume measurement and has been used to estimate accurate morphological information of different tissues, for example, bone, muscle, and articular cartilage [1719]. Additionally, the use of MRI in a residual limb morphological measurement, when common casting materials were used, was validated in previous experiments [15, 20, 21]. …”
Section: Introductionmentioning
confidence: 99%